Re-description of the poorly known sea anemone Condylanthus magellanicus Carlgren 1899 on the Argentine Patagonian coast - Garese, A.; Durán-Fuentes, J. [UNESP]; Martin, J. P.; González-Muñoz, R.; Acuña, F. H. (Springer Nature, 2025)
This paper provides the first photographs of live specimens and a re-description of the poorly known sea anemone Condylanthus magellanicus Carlgren, 1899. Condylanthus comprises only two species, C. magellanicus and C. aucklandicus Carlgren, 1924, which are considered probable synonyms by some authors. Since its original description, C. magellanicus has rarely been reported, and live specimens have never been recorded. Its distribution includes southern South America, Argentina and South Africa. Eleven specimens of C. magellanicus were collected in the intertidal zone of Península San Julián in Southern Patagonia (Santa Cruz Province, Argentina). We conducted an exhaustive morphological study, including the specimens’ internal and external anatomy, microanatomic studies, analysis of cnidocyst composition, and new details of reproductive structures. These findings contribute to an improved and clarified understanding of this poorly documented species.
Keywords: Actiniaria; Argentina; Cnidaria; Condilanthidae; Morphology; Southwest Atlantic